Pengembangan Media English Vocabulary Card Untuk Meningkatkan Minat Belajar Bahasa Inggris Di SDI Utaseko (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This type of research is research and development (R&D). The objectives of this study are 1) to design English vocabulary card media to increase interest in learning English at SDI Utaseko. 2) to test the feasibility of English vocabulary card media to increase interest in learning English at SDI Utaseko. This study uses the ADDIE model with stages of research and development consisting of 1) Analysis, 2) Design, 3) Development, 4) Implementation and 5) Evaluation). The data collection method in this study uses a questionnaire method to assess the feasibility of the English vocabulary card media. The data in this study were analyzed using quantitative descriptive. Based on the results of the research that has been done, it can be concluded that the English vocabulary card media is feasible to be used as the main media in increasing interest in learning English in grade IV students of SDI Utaseko. This can be seen based on the results of expert trials, including the following. 1) the material expert trial obtained an average value of 78.33% with the category "Feasible", then the media expert validation was carried out and a percentage of 94% was obtained, while the results of the product user trial obtained a result of 80% or was in the feasible category. Thus it can be concluded that English vocabulary card media can be used as the main media on the theme of Things in the Classroom to increase interest in learning English in grade IV students of SDI Utaseko.